Re-examining Tarbiyah Nabawi as a Preventive Step for the Dangers of Pluralism in the World of Education - M. Sholahuddin (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2024)
Islam came with the spirit of scientific progress for mankind. The Prophet Muhammad SAW as the bearer of the Islamic message with his tarbiyah system which emphasized faith, love of knowledge, beauty of morals and role models succeeded in bringing a nation that was previously left behind to become an advanced nation and become the center of scientific civilization. However, unfortunately this glory is only a memory, because Muslims themselves are starting to abandon their teachings and have forgotten the concepts established by their Prophet. Now Muslims are again facing new challenges with the emergence of pluralism which is felt to have invaded the world of education. This understanding of pluralism is certainly dangerous for the young generation of Muslims, because this understanding of pluralism instills the teachings of relativism, gives a wrong understanding of tolerance, and dwarfs Islamic law. So to fight this pluralism, it is necessary to re-implement the Nabawiyah tarbiyah concept in the education system. Because the main root of this pluralism is Muslims' ignorance of the true teachings of Islam, so they are easily influenced by outside whispers.